2005
DOI: 10.1038/sj.hdy.6800662
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and clonal diversity of an introduced pest in Chile, the cereal aphid Sitobion avenae

Abstract: In Chile, the aphid Sitobion avenae is of recent introduction, lives on cultivated and wild Poaceae, and is thought to reproduce by permanent parthenogenesis. In order to study the genetic variability and population structure of this species, five microsatellite loci were typed from individual aphids collected from different cultivated and wild host plants, from different geographical zones, and years. Chilean populations showed a high degree of heterozygosity and a low genetic variability across regions and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 56 publications
(83 reference statements)
10
81
1
Order By: Relevance
“…Other studies on S. avenae have shown the existence of such generalist genotypes, both in the U.K. and elsewhere (e.g. Chile; Figueroa et al , 2005 ), whereas similar generalist genotypes of M. persicae have also been discovered both in the U.K. ( Fenton et al , 1998b( Fenton et al , , 2005 and in Australia ( Vorburger et al , 2003a ). Studies on other aphids have further demonstrated host preference in aphids, so that the phenomenon is now no longer an issue (e.g.…”
Section: Host Preference and Clonal Selectionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies on S. avenae have shown the existence of such generalist genotypes, both in the U.K. and elsewhere (e.g. Chile; Figueroa et al , 2005 ), whereas similar generalist genotypes of M. persicae have also been discovered both in the U.K. ( Fenton et al , 1998b( Fenton et al , , 2005 and in Australia ( Vorburger et al , 2003a ). Studies on other aphids have further demonstrated host preference in aphids, so that the phenomenon is now no longer an issue (e.g.…”
Section: Host Preference and Clonal Selectionmentioning
confidence: 91%
“…Because many aphids are carried over long distances, including globally via human agency (on vehicles, ships and aircraft on infested plant material), deciding what exactly comprises a population is difficult, if not impossible ( Loxdale, 2007( Loxdale, /2008. Some species, such as M. persicae and S. avenae , are distributed globally and it may be that certain clones are also now distributed around the world ( Wilson et al , , 2002Figueroa et al , 2005 ), although they are of course still liable to mutation and selection, and hence rapid evolution.…”
Section: Displacements In Time and Spacementioning
confidence: 99%
“…Large populations may be hosted in such habitats and provide excellent resources for genetic diversification. Although sexual recombination events seem to be irrelevant, mutations and rapid selection events may maintain diversity within the habitat (Loxdale and Lushai 2003;Figueroa et al 2005).…”
Section: European D Vitifoliae Habitatsmentioning
confidence: 99%
“…Molecular markers such as microsatellites have previously proven suitable for investigating life cycles, population structure and the wax and wane of clones, such as dispersal, proliferation and mortality of clones under field conditions ( Simon et al , 1999;Haack et al , 2000;Guillemaud et al , 2003;Llewellyn et al , 2003Llewellyn et al , , 2004. Five microsatellites markers have proven sufficient to discriminate between aphid clones in the genus Sitobion because five to ten extra primer sets did not discriminate additional multilocus genotypes ( Haack et al , 2000;Llewellyn et al , 2004;Figueroa et al , 2005 ). In the present study, we utilized seven microsatellite markers to (i) confirm the hypothesis that the holocyclic lifestyle strategy is dominant for S. avenae in Denmark; (ii) investigate population differentiation and migration of Danish S. avenae , (iii) investigate seasonal changes of clonal diversity and distribution of S. avenae at the field level; (iv) determine whether aphid pathogenic entomophthoralean fungi affect population differentiation and clonal distribution of S. avenae in Danish agroecosystems; and (v) discuss future biological control strategies (conservation) of aphids in cereals based on our findings.…”
Section: Introductionmentioning
confidence: 99%